2016
DOI: 10.1177/0954405416662080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abrasive types on the surface integrity of abrasive-flow-machined surfaces

Abstract: In this article, the effect of abrasive types on the abrasive flow machining process was investigated. Four groups of abrasive media were prepared with different types of abrasives: SiC, AL 2 O 3 , B 4 C and Garnet. An experimental study was performed on DIN 1.2379 tool steel. The specimens were cut using wire electrical discharge machining and finished with the abrasive flow machining process. The results show that the white layer that formed during wire electrical discharge machining was successfully removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…There were many developments over the last few decades in the cost-effective and quality-assured manufacturing of precisely finished components for a variety of industrial applications. 1,2 There are a number of finishing processes involving the use of abrasives, for example, abrasive flow machining, 35 magneto-rheological fluid-based machining 6,7 and magnetic abrasive finishing (MAF). 8 In MAF, the finishing forces are primarily controlled by the magnetic field produced by a permanent magnet or an electromagnet.…”
Section: Introductionmentioning
confidence: 99%
“…There were many developments over the last few decades in the cost-effective and quality-assured manufacturing of precisely finished components for a variety of industrial applications. 1,2 There are a number of finishing processes involving the use of abrasives, for example, abrasive flow machining, 35 magneto-rheological fluid-based machining 6,7 and magnetic abrasive finishing (MAF). 8 In MAF, the finishing forces are primarily controlled by the magnetic field produced by a permanent magnet or an electromagnet.…”
Section: Introductionmentioning
confidence: 99%
“…67 High viscosity media gives higher deburring effects compared to medium viscosity media or low viscosity media. Gov and Eyercioglu 68 observed that AFM media synthesized with B 4 C and SiC abrasives have better surface improvement than the Al 2 O 3 and Garnet abrasives.…”
Section: Developments In Aff Processmentioning
confidence: 99%
“…The processing effect of the abrasive flow is directly related to the hardness of the abrasive particle. 27 Since the titanium alloy has a high surface hardness, silicon carbide was selected as the abrasive particles. D is the abrasive particle size, φ is the concentration of abrasive particle, t is the processing time, Ra is the measured value of the surface roughness, and Ra ′ is the predictive value.…”
Section: Design Of Abrasive Flow Machining Experimentsmentioning
confidence: 99%